Herman Voaden’s Romantic Ecology: Settler Identity and the Canadian Sublime - Gray, Nelson (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
If, in Jonathan Bate’s view, literary critics would be well served by turning their attentions to a “historical tradition of ecological consciousness,” one obvious starting point for critics of Canadian drama is with the writings of Herman Voaden. Voaden is well known to Canadian theatre scholars as a playwright and director who drew his creative inspiration from the “natural” world, and who, in the 1920s and 30s, viewed what he perceived as the Canadian wilderness as a crucial factor in the shaping of settler identity. Incorporating Bate’s advice, and drawing on insights from Northrop Frye, Val Plumwood, Christopher Manes, and Akira Lippit, this ecocritical study shows how an ecological consciousness came to the fore in Voaden’s writings and how, in his play Murder Pattern, he brings this to its most fully developed form, portraying elements in the more-than-human physical world, not as the ground for human action, but as actions in their own right: sublime agencies that measure human lives vis-a-vis the frailty of mortal desires.